Ceramic–metal composites for heat exchangers in concentrated solar power plants. (18th October 2018) - Caccia, M.; Tabandeh-Khorshid, M.; Itskos, G.; Strayer, A.; Caldwell, A.; Pidaparti, S.; Singnisai, S.; Rohskopf, A.; Schroeder, A.; Jarrahbashi, D.; Kang, T.; Sahoo, S.; et al.
Abstract The efficiency of generating electricity from heat using concentrated solar power plants (which use mirrors or lenses to concentrate sunlight in order to drive heat engines, usually involving turbines) may be appreciably increased by operating with higher turbine inlet temperatures, but this would require improved heat exchanger materials. By operating turbines with inlet temperatures above 1, 023 kelvin using closed-cycle high-pressure supercritical carbon dioxide (sCO2 ) recompression cycles, instead of using conventional (such as subcritical steam Rankine) cycles with inlet temperatures below 823 kelvin1–3, the relative heat-to-electricity conversion efficiency may be increased by more than 20 per cent. The resulting reduction in the cost of dispatchable electricity from concentrated solar power plants (coupled with thermal energy storage4–6 ) would be an important step towards direct competition with fossil-fuel-based plants and a large reduction in greenhouse gas emissions7 . However, the inlet temperatures of closed-cycle high-pressure sCO2 turbine systems are limited8 by the thermomechanical performance of the compact, metal-alloy-based, printed-circuit-type heat exchangers used to transfer heat to sCO2 . Here we present a robust composite of ceramic (zirconium carbide, ZrC) and the refractory metal tungsten (W) for use in printed-circuit-type heat exchangers at temperatures above 1, 023 kelvin9 . This composite has attractive high-temperature thermal, mechanical and chemical properties and can be processed in a cost-effective manner. We fabricated ZrC/W-based heat exchanger plates with tunable channel patterns by the shape-and-size-preserving chemical conversion of porous tungsten carbide plates. The dense ZrC/W-based composites exhibited failure strengths of over 350 megapascals at 1, 073 kelvin, and thermal conductivity values two to three times greater than those of iron- or nickel-based alloys at this temperature. Corrosion resistance to sCO2 at 1, 023 kelvin and 20 megapascals was achieved10 by bonding a copper layer to the composite surface and adding 50 parts per million carbon monoxide to sCO2 . Techno-economic analyses indicate that ZrC/W-based heat exchangers can strongly outperform nickel-superalloy-based printed-circuit heat exchangers at lower cost. A robust ceramic/refractory metal (ZrC/W)-based composite for use in heat exchangers in concentrated solar power plants above 1, 023 kelvin is described, having attractive high-temperature thermal, mechanical and chemical properties combined with cost-effective processing.